Development of a mathematics learning tool using inventive principle - Marinah Aminuddin, Farah; Shafiqah Radzuan, Anis; Zainuddin, Aznilinda; Suraya Shaharuddin, Ummi; Onn, Munirah; Mohamed, Suhana; Balqis Ismail, Herda; Hamizah Mohd Nordin, Atiqah; Fahmi Mustapa, Rijalul (International Journal of Engineering and Technology, 2018)
Gamification learning is proven to be an educational approach to nurture studentâ€™s interest to learn by using the game invented and designed with their special elements in learning environments. This project applies a systematic design approach using inventive principles to develop mathematics learning tools for primary school students. A product that gives real experiential learning to the students with versatile and innovative values developed using inventive principles, ensuring that kids have the experience of learning by doing, this product helps to develop new skills, new attitudes and new ways of thinking. Four different inventive principles which are self-service, feedback, color change and dynamization are used to produce the final product which is simpler, faster and cheaper. Since there is a significant growth of the economic world, the revolutionary is sure to occur. The scenario indicates that the possibility of ineffective teaching method and tradi-tional method of teaching are no longer suitable for this generation of kids. It attracts kids to learn mathematics using gamification as a plat-form. The project uses a color sensor that replaces the numbers. The color sensor then sends the information to the microcontroller. The final working prototypes named MEGO acronym for Mathematics Education Go. Â